Assessment of browsed plants in a sub-tropical forest frontier by means of fuzzy inference. (15th April 2019) - Dechnik-Vázquez, Yanus A.; García-Barrios, Luis; Ramírez-Marcial, Neptalí; van Noordwijk, Meine; Alayón-Gamboa, Armando
Abstract: Browsing of forest frontiers by cattle in sub-tropical landscapes is detrimental to ecosystem health, but essential to smallholder livelihoods. We described a silvopastoral landscape, searching for browsed plants to assess how much of the forest is actually used for this end, and also searching for potential new useful species for silvopastoral purposes. The first objective was accomplished through a floristic description, making observations of individuals with browsing marks. Information from interviews, bromatological analyses and vegetative propagation tests further complemented this information to achieve the second objective. We classified the results using Fuzzy Inference Systems (FISs). A great variety of nutritious browsed plants was found, distributed across various types of vegetation, growth habits and taxonomic groups: forest frontiers already are like silvopastoral systems. Various plants like Acalypha leptopoda, Montanoa tomentosa and Verbesina perymenioides are interesting prospects for further intensification of silvopastoral systems. Highlights: The forest frontier in a sub-tropical landscape is plenty with browsed species (>100). Many of these plants have potential for silvopastoral intensification, like V. perymenioides and A. leptopoda. Forest frontiers already are like silvopastoral systems. This might be why smallholders often don't pursue the latter. Fuzzy inference methods are very useful for systematization of knowledge for environmental management.